Factors associated with the perception of resentment towards the Chinese in Latin America during the first wave of the COVID‑19 pandemic - Alvarez‑Risco, Aldo (2024)
[Introduction] Resentment towards the Chinese population was perceived during the first months of the pandemic because the pandemic/disease started in that country. [Objective] To determine the factors associated with the perception of resentment towards the Chinese in Latin America during the first wave of the COVID-19 pandemic. [Methodology] Analytical cross-sectional study conducted during the second semester of the pandemic in more than a dozen countries. Four questions were asked about the perception of resentment towards the Chinese (Cronbach’s Alpha: 0.88); those with the highest scores on the sum of the four questions were considered to have "more resentment towards the Chinese," and descriptive and analytical statistics were obtained. [Results] Of the 7721 respondents, in the multivariate analysis, it was found that there was a difference according to the country; compared to Peru, those who had more resentment towards the Chinese were those residing in Paraguay (aPR: 1.29; 95%CI: 1.17–1.42; p-value<0.001) and Bolivia (aPR: 1.52; 95%CI: 1.37–1.68; p-value<0.001), while Chile (aPR: 0.78; 95%CI: 0.69–0.88; p-value<0.001) had less resentment: 0.69–0.88; p-value<0.001), Mexico (aPR: 0.68; 95%CI: 0.57–0.80; p-value<0.001), Panama (aPR: 0.71; 95%CI: 0.59–0.86; p-value<0.001) and Costa Rica (aPR: 0.64; 95%CI: 0.49–0.85; p-value=0.002).